Le défi des outils numériques dans la scolarisation des élèves avec autisme : entre les besoins cognitifs des élèves et les approches pédagogiques des enseignants - Camelia-Mihaela Dascalu; Philippe Garnier (Recherches en Éducation)
The learning difficulties facing students with autism not only require an adaptation of the learning environment, (strategies and tools) but also require a personalized adaptation taking into account the specific skills and needs of students with autism. This personalized adaptation will be inserted into the collective learning of the class. If many studies have shown the interest of using information and communication technologies (ICT) in education for students with autism, these refer to making digital tools compatible with the teacher’s adapted pedagogical approach, in order for them to be fully employed into school practice. As a matter of fact, far from being a homogenous category, students with autism each have their own particularities, hence the need for information technology tools that are adapted to each pupil’s profile, whilst being in tune with the teacher’s pedagogical style. This article presents a collaborative research between a special teacher and a few researchers, concerning the introduction of a very personalized information technology tool. The grounded theory approach makes the process of inserting the information technology tools into a special teaching for students with autism, more intelligible.